2019
DOI: 10.11114/bms.v5i4.4571
|View full text |Cite
|
Sign up to set email alerts
|

Personalised Content in Mobile Applications and Purchase Intentions: An Exploratory Study

Abstract: This study aims to examine how personalised content affects consumers’ purchase intentions in the mobile beauty shopping applications within the UK. Based on previous studies personalised content on mobile beauty applications influences consumer behaviour in terms of mobile application convenience, m-loyalty and emotions. In-depth semi-structured interviews were conducted with 12 females between the ages of 18-35 who live in the UK. According to the results, personalised content has a positive influence on bot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 44 publications
(74 reference statements)
0
4
0
Order By: Relevance
“…Personalization means that the communicators create content whilst considering factors such as who the audience is, how and when the audience reads the content, and the devices used to read the content. On top of that, personalized content has a positive influence on mobile convenience and loyalty [35]. Against this backdrop, this study proposes that the personalization of content is a success criterion for effective social media health promotion.…”
Section: Personalization Of Contentmentioning
confidence: 92%
“…Personalization means that the communicators create content whilst considering factors such as who the audience is, how and when the audience reads the content, and the devices used to read the content. On top of that, personalized content has a positive influence on mobile convenience and loyalty [35]. Against this backdrop, this study proposes that the personalization of content is a success criterion for effective social media health promotion.…”
Section: Personalization Of Contentmentioning
confidence: 92%
“…As internet platforms give Gen Z the ability to skip marketing promotions that interfere with their pleasure, Tabassum et al (2020) underlined the need of putting real and relatable entertainment into video marketing. According to Saxena et al (2018), compared with informational content, the value of marketing content increases when it is personalised (Konstantoulaki et al, 2019) and it is coupled with entertainment. A study by Eid et al (2020) states that entertainment has a bigger influence compared with other factors.…”
Section: Expertisementioning
confidence: 99%
“…Srivastava and Thaichon (2023) noted that online personalization enhances consumer satisfaction and could create a pleasant shopping environment for consumers while Lee and Park (2009) also found a positive relationship between personalization and purchase intention. Some other studies focused on online advertisement (Odoom, 2022) and mobile applications (Konstantoulaki et al, 2019) but also found personalized services to positively influence customers purchase intentions. Therefore, the following hypothesis has been developed: H 5.…”
Section: 2mentioning
confidence: 99%